Utilitarianism and Prison Abolition: A Normative Perspective - Beraha, Marina (ETHICS IN PROGRESS, 2026)
This paper develops a utilitarian case for prison abolition grounded on utilitarianism’s commitment to the reduction of pain, challenging the traditional forward-looking utilitarian justifications of punishment, whose empirical foundations are increasingly contested. To construct the utilitarian abolitionist argument, traces of an abolitionist theory are identified in Bentham’s penal thought, especially in his neglected analysis of indirect legislation as a means of crime prevention. His theoretical analysis is integrated with contemporary debates on punishment, incarceration and restorative justice. The paper argues that a consistently utilitarian approach should prioritize harm reduction through social restructuring, transformative approaches, and restorative responses to wrongdoing, rather than relying on incarceration and deterrence-centred punishment.